2012
DOI: 10.1371/journal.pone.0051496
|View full text |Cite
|
Sign up to set email alerts
|

Liver Function Tests and Risk Prediction of Incident Type 2 Diabetes: Evaluation in Two Independent Cohorts

Abstract: BackgroundLiver function tests might predict the risk of type 2 diabetes. An independent study evaluating utility of these markers compared with an existing prediction model is yet lacking.Methods and FindingsWe performed a case-cohort study, including random subcohort (6.5%) from 38,379 participants with 924 incident diabetes cases (the Dutch contribution to the European Prospective Investigation Into Cancer and Nutrition, EPIC-NL, the Netherlands), and another population-based cohort study including 7,952 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 32 publications
2
27
1
Order By: Relevance
“…Abbasi and colleagues found no significant association in one of their cohorts of men and women aged 28-75 years [13]. In the Atherosclerosis Risk in Communities study [8], low serum albumin was associated with an increased risk of type 2 diabetes among men and women aged 45-65 years in analyses [6,11,12], cancer mortality [6] and allcause mortality [11].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Abbasi and colleagues found no significant association in one of their cohorts of men and women aged 28-75 years [13]. In the Atherosclerosis Risk in Communities study [8], low serum albumin was associated with an increased risk of type 2 diabetes among men and women aged 45-65 years in analyses [6,11,12], cancer mortality [6] and allcause mortality [11].…”
Section: Discussionmentioning
confidence: 96%
“…A limited number of prospective studies have been published reporting on the associations between baseline serum albumin concentrations and risk of type 2 diabetes [8,13,14], but their results have been inconsistent. Whereas some studies have shown inverse associations [13,14], other studies have found no association between serum albumin and type 2 diabetes [8,13], giving rise to uncertainty regarding the nature of the association. To help characterise and quantify more reliably the nature and magnitude of the association, we report a detailed assessment of the association of serum albumin concentration with incident type 2 diabetes in a population-based sample of 1,785 non-diabetic men from eastern Finland.…”
Section: Introductionmentioning
confidence: 99%
“…The hope of groups investigating other biomarkers is that they will enhance prediction further. Our review suggests that over a time horizon of 5–10 years, additional biomarkers have failed to improve prediction metrics over a model consisting of traditional diabetes predictors, glucose and HbA1c [51][4][40,52] which are, of course, measures used in the diagnosis of diabetes. In this context, the utility of biomarkers (or variables) is clinically-relevant for predicting the future risk of T2D [4,16,48,49], while individuals are not necessarily in prediabetes state.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study from the Netherlands, liver function tests, including ALT, AST, GGT and albumin, modestly improved the prediction of incident diabetes in models with fasting glucose and other readily available clinical variables . In that report, liver function tests had little incremental predictive value after adding HbA 1c to the model . In the present study, ALT improved discrimination after considering glucose tolerance.…”
Section: Discussionmentioning
confidence: 96%